2002
DOI: 10.1590/s0104-66322002000400011
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of vinyl acetate emulsion polymerization in a pulsed tubular reactor: comparison between experimental and simulation results

Abstract: -A new reactor, the pulsed sieve plate column (PSPC), was developed to perform continuous emulsion polymerization reactions. This reactor combines the enhanced flexibility of tubular reactors with the mixing behavior provided by sieved plates and by the introduction of pulses that is important to prevent emulsion destabilization. The main objective of this work is to study the kinetics of vinyl acetate (VA) emulsion polymerization reactions performed in this PSPC. Therefore, both experimental studies and react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…The mathematical model is based on a previous model of Sayer et al (2002a) of emulsion homopolymerization reactions in the PSPC. In the elaboration/complementation of this model the following assumptions are made: § Monomer concentrations in polymer particles, monomer droplets and aqueous phase are at thermodynamic equilibrium and are computed using the iterative procedure proposed by Omi et al (1985).…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…The mathematical model is based on a previous model of Sayer et al (2002a) of emulsion homopolymerization reactions in the PSPC. In the elaboration/complementation of this model the following assumptions are made: § Monomer concentrations in polymer particles, monomer droplets and aqueous phase are at thermodynamic equilibrium and are computed using the iterative procedure proposed by Omi et al (1985).…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…The balance equations of continuous homopolymerization reactions in the PSPC were presented in Sayer et al (2002a) and are shown in the Appendix. In the present work the following average coefficients were used to describe the copolymerization reactions:…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Em ambos os casos, as pulsações causam turbulências suficientes para dificultar a deposição das partículas de polímero nas paredes e nos internos do reator, evitando entupimentos e incrustações, além de propiciar uma boa mistura radial para o transporte de calor. Em trabalhos anteriores do grupo CARVALHO et al, 2006a;CARVALHO et al, 2006b;CARVALHO et al, 2006c;PALMA, 2002;PALMA e GIUDICI, 2001;PALMA e GIUDICI, 2003;PALMA et al, 2001a;PALMA et al, 2001b;SALLARÉS et al, 2004;SAYER e GIUDICI, 2002a;SAYER e GIUDICI, 2002b;SAYER et al, 2002a;SAYER et al, 2002b), foi estudado o uso da coluna pulsada com pratos perfurados (CPPP) para a realização de reações de homopolimerização de acetato de vinila e de copolimerização de acetato de vinila e acrilato de butila em emulsão. Neste caso, as pulsações produzidas no meio reagente evitam não só a formação de depósitos, decorrentes da desestabilização da emulsão, como também gradientes radiais de temperatura e de concentração.…”
Section: Colunas Pulsadasunclassified